التصور التربوي الإسلامي لدور المعلم في الحد من عنف تلاميذ الحلقة الثانية من التعليم الأساسي: دراسة تحليلية - فايد، هيثم عبدالله عبدالمجيد; الغنام، محمد عبدالقوي شبل; جزر، شحات غريب حسن; درويش، رمضان محمود أحمد (جامعة الأزهر - كلية التربية, 2022)
هدفت الدراسة إلى بيان التصور التربوي الإسلامي لدور المعلم في الحد من عنف تلاميذ الحلقة الثانية من التعليم الأساسي، واستخدمت المنهج الأصولي والمنهج الوصفي، وتوصلت نتائجها إلى أن العنف المدرسي: مجموعة من السلوكيات العدوانية بين التلاميذ أنفسهم وبينهم وبين المدرسين، أو أنه السلوكيات غير الملائمة والمستهجنة إلى تتسبب في ظهور الاضطرابات النفسية والسلوكية في البيئة الصفية داخل المدرسة، وتتنوع مظاهر العنف المدرسي إلى الاعتداء البدني، الاعتداء اللفظي، الاعتداء النفسي، وتتعدد الأسباب المسببة والمفسرة للعنف المدرسي: ما بين الأسباب التربوية والنفسية، والأسباب الاجتماعية، والأسباب الثقافية، والأسباب الاقتصادية، وكلها أسباب متداخلة فيما بينها، كما توصلت إلى أن من أهم ما يجب أن يكون عليه المعلم من آداب لوقاية التلاميذ من العنف المدرسي: أن يتحلى بالقدوة، والصبر، والعدل، والرحمة، والنصح والإرشاد والتوجيه، والرفق بالتلاميذ وإكسابهم مهارات الحوار والمناقشة، كما تتحدد أدوار المعلم في مواجهة عنف التلاميذ إذا خرجوا عن آداب العلم والتعليم بالتدرج في استخدام العقوبة بدءًا بالتغافل عن الخطأ، والتلميح بالأخطاء، والإعراض عن المخطئ، وعتابه، واستخدام التأنيب والتوبيخ، وحرمان المخطئ، والتلويح بالعقوبة، وضرب الالمصر على خطئه. This study aimed to identify the Islamic educational perception of the role of the teacher in reducing the violence of students of the second cycle of basic education and used the fundamentalist and descriptive approach. The results revealed that school violence is a set of aggressive behaviors between the students themselves and between them and the teachers, or it is inappropriate and reprehensible behaviors which cause the emergence of psychological and behavioral disorders in the classroom environment within the school. The manifestations of school violence vary to physical abuse, verbal abuse, psychological abuse. The causes and explanations of school violence are multiple: educational and psychological assets, social assets, cultural assets, and economic assets; all of which are intertwined with each other, and it was also concluded that one of the most important etiquettes that the teacher should have in teaching science is to be a role model, have patience, have justice, mercy, advice, guidance, and direction, kindness to students and providing them with skills of dialogue and discussion. Confronting students’ violence if they deviate from the ethics of science and education by gradual use of punishment, starting with overlooking the student’s mistake, and alluding to errors in teaching. For the wrong student, turning away from the wrong student, reprimanding the wrong student, using reprimand and reprimanding, depriving the wrong student, threatening and intimidating the wrong student with punishment, and hitting the student who persists in mistake.
Keywords: التربية الإسلامية -- العنف المدرسي -- طلبة التعليم الأساسي -- مصر